A atuação clínica de psicólogas negras do município de Natal: notas sobre aquilombamento e cuidado - Costa, Marcela Andressa (2024)
In this research, I start from my experience as a black woman and clinical psychologist and the concerns that emerged from this place. In this study, I propose to investigate the challenges present in the construction of clinical practices by black psychologists in the municipality of Natal/RN and the possible paths for a decolonized and anti-racist psychology. I take into account that the historical process of Brazilian society is determined by the colonization and effects of coloniality that structure the order established in the classification and social hierarchy. Thus, racism is a phenomenon of this colonization, becoming structuring of the modes of subjectivation, permeating and crossing concrete relations in the areas of economics, law, politics and, ideologically, building the racist, oppressive and exclusionary social imagination (Silvio Almeida, 2019). Knowledge production is also crossed by the effects of coloniality for the purpose of building “universal” thinking, but based on a eurocentric reason. Psychology, as scientific knowledge, is also constituted in the foundations of eurocentrism, racism and epistemic sexism. This research aims to understand the repercussions of racism in the process of formation and professional performance of black psychologists in the field of the clinic. I analyze the life trajectories and formative processes of professionals and their effects on clinical practice to know the challenges in our experiences in a historically colonized clinic and the construction of collective resistance in facing racism. To do so, this qualitative research conducted interviews to grasp the narratives of black psychologists working at the clinic. 5 professionals that work in the municipality of Natal were interviewed. As results, research proposes the exercise of new clinical practices in understanding the impact of racism on the mental health of the black population. Finally, I discuss how clinical psychology can be built from a perspective of joining into quilombos groups and processes of caring and the importance of this for an ethical-political project decolonizing and anti-racist.